The genus Heteragrion (Odonata: Zygoptera) in Northwestern Colombia, with the description of Heteragrion tatama sp. nov. - Bota-Sierra, Cornelio Andrés; Novelo-Gutiérrez, Rodolfo (Zootaxa, 2017)
The Neotropical forest specialist genus Heteragrion counts with 54 species and one subspecies described to date, eight of which have been recorded from Colombia. Here, information on Heteragrion species resulting from ten years of exploration of northwestern Colombia and examination of museum collections, including types and species from Central America, is presented. A new species endemic to the Tatamá National Park in the western Andes, Heteragrion tatama sp. nov. is described, as well as the female of Heteragrion aequatoriale Selys, 1886. Heteragrion calendulum Williamson, 1919 was rediscovered, a century after its first collection, which allowed us to compare it with Heteragrion atrolineatum Donnelly, 1992, and to conclude that the latter species is its junior synonym. We present pictures of female prothoracic intersternite, which offer valuable taxonomic information. The variation in coloration patterns for H. aequatoriale and Heteragrion mitratum Williamson, 1919 is discussed, and maps with new distributional data, a taxonomic key, natural history notes and photographs of the Heteragrion species distributed west of the Magdalena valley in Colombia, are also provided.